Insights into Tumor Microenvironment (TME) and the Nano Approaches to Suppress Tumor Growth - Perpetua Takunda Kutoka; Theodora Amanda Seidu; Vongai Baye; Amari Mohamed Khamis; Charos Tuychi qizi Omonova; Bo Wang (Elsevier, 2022)
Cancer, the second major cause of death after cardiovascular disease has been reported to have resulted in over 10 million deaths worldwide per year, on average. Resistance to therapeutic interventions is a definitive characteristic of cancer, where acquired resistance has become a challenge that has significantly reduced the anti-tumor efficiency of cancer therapy. The tumor microenvironment (TME) is heavily responsible for these cancer cell-targeted drug delivery system challenges due to its abundant physiological and pathological barriers that impair the tumoral penetration and distribution of nanotherapeutics. However, these unique TME characteristics also make the TME an attractive therapeutic target and a focus of intense research in the development of antitumor nanomedicine strategies that can directly target or modulate it. In this review, we summarize the strategies developed to target the TME to overcome the obstacles against nano-drug delivery and consequently improve anti-tumor efficiency.